STUDENT SEXUAL ORIENTATION AND THE RELATIONSHIP WITH PARENTING STYLES AND PEERS ATTACHMENT - Nurzea Hakiki; Nur Islamiah; Alfiasari (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2022)
Sexual orientation deviation is one of the problems often found in adolescents today. Sexual orientation in adolescents is one of the critical components in adolescent development because it involves adolescents' identity, interests, and sexual behaviour when will enter adulthood. Deviations Within the boundaries of the ideology and culture of the nation, this deviation from sexual orientation will cause developmental disorders in adolescents, and it is necessary to identify the root of the problem so that we can take preventive action. This study aimed to analyze the condition of student sexual orientation and further analyze its relationship with family characteristics, student characteristics, parenting styles, and peer attachment. This research is quantitative research with a survey method. The examples in this study were 272 students of the Vocational School of the Bogor Agricultural University who had complete parents with a proportion of 182 women and 90 men. The sampling technique used in this research is purposive sampling. The correlation test results showed that the sex of students and family size were related to sexual orientation. G that parenting style on the dimensions of rejection and coercion is related to sexual orientation. In addition, peer attachment to the dimension of alienation relates to student sexual orientation. Negative parenting styles and peer attachment have a relationship with sexual orientation. Therefore, parents should avoid negative parenting styles and control their children's environment so that sexual orientation deviations do not occur. Negative parenting styles in rejection, chaos and parental coercion tend to be associated with deviations in student sexual orientation. Likewise, the dimension of a perceived alienation from peer relationships also relates to student sexual orientation deviations.